Analisis Penyelenggaraan Pembangunan Partisipatif di Desa Lauwa Kecamatan Belopa Utara Kabupaten Luwu - Nurfadilla Nurfadilla; Rasyid Thaha; Andi Lukman Irwan (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2019)
This research aims to find out how the implementation of participatory development in Lauwa Village Belopa Utara District Luwu District and to know the factors that influence the implementation of participatory development in Lauwa Village Belopa Utara District Luwu District. The type of research used is descriptive analysis that is a type of research that aims to provide a systematic, factual and accurate description of existing data in the field about the implementation of partial development in Lauwa Village Belopa Utara District Luwu District. Data were collected using observation techniques, in-depth interviews, and literature studies. The results of this study indicate that the implementation of participatory development in Desa Lauwa has been well implemented from every process, including the process of development planning, development and evaluation/monitoring, but to achieve more active participation needs to be improved again in each process. Then there are several factors that influence the implementation of participative development in Lauwa village that is supporting and inhibiting factors, namely: a) Supporting Factors: Leadership of Village Head, Community Participation, Activity of Facilitator, Availability of Budget and the existence of Clear Regulation; b) Inhibiting Factors: Land Acquisition, Non-Governmental Organizations and Human Resources.